Prediksi Usia Simpan Amunisi Kaliber Kecil dan Uji Performa Balistiknya: Studi Di Gudang Senjata AAU - Jati, Rhestu Pradhipta; La Ore, Muhammad Sakti (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
Research has been carried out on small caliber ammunition (MU1-JHP, MU2-TJ, and MU5-TJ) produced by PT. Pindad to predict the remaining shelf life of ammunition with the propellant stability test method and calculate the shelf life using the Berthelot equation. In addition, ballistic performance tests are also carried out to determine the feasibility of ammunition with predetermined specification standards. From the research results showed that on the MU1-JHP ammunition caliber 9 mm 2010 (the oldest lot number in stock in the warehouse for the same type) and lot number 2015 (youngest) was predicted that the remaining shelf life was 14.69 and 16.16 years, respectively. The MU2-TJ ammunition caliber 7.62 mm lot number 1992 (oldest) and 1994 (youngest) was predicted the remaining shelf life was 4.41 years and 5.88 years, respectively. The MU5-TJ ammunition caliber 5.56 mm lot number 2015 (oldest) and 2017 (youngest) was predicted to have a remaining shelf life of 19.10 years and 11.75 years, respectively. The results of the ballistic performance test (gas pressure, speed and accuracy) of small caliber ammunition on the MU1-JHP ammunition caliber 9 mm lot number 2010 and 2015 both still meet the standard specifications. The ballistic performance of the MU2-TJ ammunition caliber 7.62 mm lot number 1992 and 1994 both did not meet the specifications. The ballistic performance of the MU5-TJ ammunition caliber 5.56 mm lot number 2015 and 2017 both still meet the standard specifications.